One-component urethane resin composition and peeling prevention method

JP2025025533APending Publication Date: 2025-02-21KONISHI CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023130375
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-21

Smart Images

  • Figure 2025025533000001_ABST
    Figure 2025025533000001_ABST
Patent Text Reader

Abstract

To provide a one-component urethane resin composition with excellent weather resistance in addition to excellent strength and curability through urethane bonding.SOLUTION: A one-component urethane resin composition comprises an isocyanate group-containing urethane prepolymer (A), a compound (B) with an oxazolidine ring, a neutral hindered amine-based light stabilizer (C), and an acidic curing accelerator (D).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a one-component urethane resin composition used in a method for preventing peeling. [Background technology]

[0002] For example, as described in Patent Document 1, a resin composition for forming an anti-peeling layer is known which is used in a construction method for forming an anti-peeling layer on the surface of a concrete structure or a wall surface to which tiles are attached, thereby preventing the concrete pieces or tiles from peeling off, and which contains a urethane prepolymer, a compound having an oxazolidine ring, and an acidic curing accelerator.

[0003] Such a resin composition for forming a peeling prevention layer is required to have both hardening properties that allow it to harden immediately after application and weather resistance that prevents deterioration even in environments exposed to rain, wind, ultraviolet rays, etc.

[0004] As a component for improving weather resistance, it is considered to use a hindered amine light stabilizer. However, as described in Patent Document 2, for example, when a hindered amine light stabilizer is used together with an acidic curing accelerator, there is a problem that the curing rate slows down and the curability deteriorates. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2011-252292 A [Patent Document 2] JP 2007-063551 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a one-component urethane resin composition which is excellent not only in strength and curability due to urethane bonds but also in weather resistance. [Means for solving the problem]

[0007] That is, the one-component urethane resin composition and the method for preventing peeling according to the present invention are as follows. [1] An isocyanate group-containing urethane prepolymer (A), A compound (B) having an oxazolidine ring; A neutral hindered amine light stabilizer (C); an acidic hardening accelerator (D); A one-component urethane resin composition comprising: [2] The one-component urethane resin composition according to [1], further comprising a thixotropy-imparting agent (E). [3] The one-component urethane resin composition according to [2], wherein the thixotropy-imparting agent (E) contains silica or amide. [4] The one-component urethane resin composition according to any one of [1] to [3], wherein the acidic curing accelerator (D) is an acidic phosphate ester compound (D-1). [5] The one-component urethane resin composition according to [4], wherein the acidic phosphorus ester compound (D-1) is a polyether phosphoric acid ester. [6] A method for preventing peeling, comprising the step of applying the one-component urethane resin composition according to any one of [1] to [5] to a concrete structure and / or a wall surface to which tiles are attached, to form a peeling prevention layer that prevents the concrete pieces and / or tiles from peeling off from the wall surface. [7] The method for preventing peeling according to [6], further comprising the step of applying a primer to the wall surface to form a primer layer before applying the one-component urethane resin composition. [8] The method for preventing peeling described in [7], characterized in that after forming the peeling prevention layer, it includes a step of applying a top coat onto the peeling prevention layer to form a top coat layer. [9] The method for preventing peeling according to any one of [6] to [8], characterized in that a glass cloth and / or a fiber knitted mesh is placed on the wall surface, and then the one-component urethane resin composition is applied to form a peeling prevention layer in which the glass cloth and / or the fiber knitted mesh is embedded. Effect of the Invention

[0008] According to the present invention, it is possible to provide a one-component urethane resin composition which is excellent not only in strength and curability due to urethane bonds but also in weather resistance. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is an explanatory diagram of a peeling prevention method according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The one-component urethane resin composition according to this embodiment will be described below. The one-component urethane resin composition according to this embodiment contains an isocyanate group-containing urethane prepolymer (A), a compound having an oxazolidine ring (B), and an acidic curing accelerator (D).

[0011] The isocyanate group-containing urethane prepolymer (A) undergoes crosslinking and hardening when the isocyanate group reacts with water (humidity). The isocyanate group-containing urethane prepolymer (A) can be obtained, for example, by reacting a polyol with a polyisocyanate under conditions in which the isocyanate groups of the polyisocyanate are in excess relative to the hydroxyl groups of the polyol, and has an isocyanate group at the end of the urethane prepolymer. A reaction catalyst may be used in this reaction.

[0012] Examples of the polyol that can be used include polypropylene glycol, polyethylene glycol, and polytetramethylene glycol. The molecular weight of the polyol is preferably, for example, from 500 to 5000, and more preferably from 1000 to 3000. Such polyols can be purchased as commercial products sold by various chemical manufacturers. Examples of polyisocyanates include compounds having two or more isocyanate groups such as diisocyanates, and examples of such polyisocyanates include aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates. Specific examples include 1,6-hexamethylene diisocyanate, 1,5-pentamethylene diisocyanate, 1,4-tetramethylene diisocyanate, 2,2,4-trimethyl-1,6-hexamethylene diisocyanate, 2,4,4-trimethyl-1,6-hexamethylene diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethylene xylylene diisocyanate, norbornane diisocyanate, and 1,4-cyclohexidyl diisocyanate. Commercially available products provided by various chemical manufacturers can be used as such polyisocyanates. As the reaction catalyst, for example, an organometallic compound such as zirconium 2-ethylhexanoate can be used. The content of the isocyanate group-containing urethane prepolymer (A) in the one-component urethane resin composition is preferably 20% by mass or more and 70% by mass or less, more preferably 30% by mass or more and 60% by mass or less, and even more preferably 40% by mass or more and 50% by mass or less.

[0013] As the compound (B) having an oxazolidine ring, for example, oxazolidine and its derivatives can be widely used. More specifically, examples of the compound include urethane bond-containing oxazolidine compounds and ester group-containing oxazolidine compounds obtained by reacting a hydroxyl group of a compound having a hydroxyl group and an oxazolidine ring with an isocyanate group of an organic isocyanate compound or a carboxyl group of an organic carboxylic acid compound, as well as oxazolidine silyl ethers and carbonate group-containing oxazolidines. Compounds having a urethane group (urethane bond) and an oxazolidine ring are preferred because they are easy to produce and have a low viscosity.

[0014] These compounds can be synthesized by conventionally known methods. For example, in the case of a urethane bond-containing oxazolidine compound, specifically, a hydroxyl group of a compound having a hydroxyl group and an oxazolidine ring and an isocyanate group of an isocyanate compound are used so that the molar ratio of isocyanate group / hydroxyl group is in the range of 0.9 to 1.2, preferably 0.95 to 1.05, and reacted at a temperature of 50 to 100° C. in the presence or absence of an organic solvent.

[0015] The isocyanate compound used in the synthesis of the urethane bond-containing oxazolidine compound may be the same as the polyisocyanate used in the synthesis of the above-mentioned isocyanate group-containing urethane prepolymer (A). It is preferable to use an aliphatic organic polyisocyanate, more preferably at least one selected from the group consisting of isophorone diisocyanate and hexamethylene diisocyanate, and particularly preferably hexamethylene diisocyanate, in order to keep the crystallinity of the urethane group-containing oxazolidine compound low and to obtain a compound with excellent solubility.

[0016] It is preferable that the compound having an oxazolidine ring does not substantially have, in the molecule, a functional group that reacts with the isocyanate group of the isocyanate group-containing urethane prepolymer (A) at room temperature of 5 to 35°C.

[0017] From the viewpoint of suppressing foaming, the content of the compound (B) having an oxazolidine ring is preferably such that the active hydrogen of the secondary amino group regenerated by hydrolysis of the compound having an oxazolidine ring is 0.3 equivalents or more, and more preferably 0.5 to 1.5 equivalents, per 1.0 equivalent of isocyanate groups in the isocyanate group-containing urethane prepolymer (A). The content of the compound (B) having an oxazolidine ring in the one-component urethane resin composition is preferably 10% by mass or more and 40% by mass or less, more preferably 15% by mass or more and 35% by mass or less, and even more preferably 20% by mass or more and 30% by mass or less.

[0018] The acidic curing accelerator (D) may be, for example, one that opens an oxazolidine ring, and is acidic (for example, pKa is 5 or less). Specific examples include formic acid, acetic acid, propionic acid, caproic acid, oxalic acid, succinic acid, adipic acid, 2-ethylhexanoic acid, octenoic acid, lauric acid, oleic acid, stearic acid, maleic acid, phthalic acid, benzoic acid, salicylic acid, and their acid anhydrides, acidic phosphate compounds, or PTSI (p-toluenesulfonyl isocyanate) and hydrolysates of PTSI, and it is preferable to use an acidic phosphate compound, and more preferably to use a polyether phosphate, which is an acidic phosphate compound. The content of the acidic curing accelerator (D) in the one-component urethane resin composition is preferably 0.05% by mass or more and 10% by mass or less, more preferably 0.1% by mass or more and 8% by mass or less, and even more preferably 0.2% by mass or more and 4% by mass or less.

[0019] The one-component urethane resin composition according to this embodiment further contains a neutral hindered amine-based light stabilizer (C, also referred to as a neutral hindered amine-based light stabilizer). Neutral here refers to a stabilizer having a pKb of more than 5.1, more preferably a pKb of 6 or more, and even more preferably a pKb of 8 or more. The content of the neutral hindered amine light stabilizer (C) in the one-component urethane resin composition is preferably 0.1 mass% or more and 5 mass% or less, more preferably 0.3 mass% or more and 4 mass% or less, and even more preferably 0.5 mass% or more and 3 mass% or less.

[0020] As commercially available products of the (C) neutral hindered amine-based light stabilizer, for example, those having the structures shown in [Chemical Formula 1] or [Chemical Formula 2] below can be used.

[0021] [ka] Compound name: Decanedioic acid, bis(2,2,6,6-tetramethyl-1-(octyloxy)-4-piperidinyl)ester, reaction products with 1,1-dimethylethylhydroperoxide and octane

[0022] [ka] Compound name: 2,4-bis[N-Butyl-N-(1-cyclohexyloxy-2,2,6,6-tetramethylpiperidic-4-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-triazine

[0023] Examples of commercially available products include Tinuvin 123 (manufactured by BASF, pKb = 9.6), Tinuvin 152 (manufactured by BASF, pKb = 7.0, 9.4), and Tinuvin 249 (manufactured by BASF, pKb = 8.0).

[0024] By using the neutral hindered amine light stabilizer (C) in this manner, even when an acidic curing accelerator is used, the resin composition according to this embodiment can be prevented from having a slow curing rate, and therefore, the sufficient strength and curability due to the urethane resin, and further the weather resistance due to the hindered amine light stabilizer, can all be within optimal ranges.

[0025] The one-component urethane resin composition according to the present embodiment may further contain a solvent and other additives in addition to the above-mentioned components. However, the addition of a solvent and other additives is not essential. The solvent may be any solvent capable of dissolving or dispersing the above-mentioned components and not inhibiting the curing reaction of the one-component urethane resin composition, and any solvent generally used in one-component urethane resin compositions may be used without problems. Specific examples of the solvent include naphthene-based solvents and glycol ether-based solvents. Examples of glycol ether-based solvents include diethylene glycol dimethyl ether and propylene glycol monomethyl ether. The solvent content of the one-component urethane resin composition is preferably 0.5% by mass or more and 20% by mass or less, more preferably 1% by mass or more and 15% by mass or less, and even more preferably 2% by mass or more and 10% by mass or less.

[0026] Other additives can be added as appropriate depending on the purpose, and examples thereof include isocyanurates, isocyanates, thixotropic agents, ultraviolet absorbers, antioxidants, and antifoaming agents.

[0027] Isocyanurate bonds with the isocyanate group-containing urethane prepolymer (A) to form crosslinks when the one-component urethane resin composition is cured, and its addition further improves the strength of the cured composition. Examples of isocyanurates include trimers of the compounds listed below, i.e., compounds produced by condensation of three molecules, and hydrogenated products thereof. The three molecules constituting the trimer may be the same or different. Examples of compounds constituting the isocyanurate compound include 1,6-hexamethylene diisocyanate, 1,5-pentamethylene diisocyanate, 1,4-tetramethylene diisocyanate, 2,2,4-trimethyl-1,6-hexamethylene diisocyanate, 2,4,4-trimethyl-1,6-hexamethylene diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethylene xylylene diisocyanate, norbornane diisocyanate, and 1,4-cyclohexidyl diisocyanate. The isocyanurate content of the one-component urethane resin composition is preferably from 1% by mass to 25% by mass, more preferably from 5% by mass to 20% by mass, and even more preferably from 10% by mass to 15% by mass.

[0028] Examples of the isocyanate include at least one of 1,6-hexamethylene diisocyanate, 1,5-pentamethylene diisocyanate, 1,4-tetramethylene diisocyanate, 2,2,4-trimethyl-1,6-hexamethylene diisocyanate, 2,4,4-trimethyl-1,6-hexamethylene diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethylene xylylene diisocyanate, norbornane diisocyanate, 1,4-cyclohexidyl diisocyanate, and hydrogenated XDI (cyclohexane-1,2-diylbis(methylene)diisocyanate).

[0029] The thixotropy-imparting agent adjusts the viscosity of the one-component urethane resin composition to an appropriate range in order to suppress dripping when the one-component urethane resin composition is applied to a wall surface or the like and to improve workability during application. Specific examples of the thixotropy-imparting agent include particulate silica and amide. The content of the thixotropy-imparting agent in the one-component urethane resin composition is preferably 0.1% by mass or more and 15% by mass or less, more preferably 0.4% by mass or more and 10% by mass or less, and even more preferably 1% by mass or more and 8% by mass or less. Examples of particulate silica include fumed silica and finely powdered silica, and surface-treated finely powdered silica is preferred. Examples of surface treatment include dimethyldichlorosilane, hexamethyldisilazane, silicone oil, etc. When silica is used as a thixotropic agent, the content of silica is preferably 0.5% by mass or more and 20% by mass or less, more preferably 1% by mass or more and 10% by mass or less, and even more preferably 2% by mass or more and 7.5% by mass or less. Examples of amides include reaction products produced by condensation reaction of fatty acids (stearic acid, ricinoleic acid, oleic acid, oxystearic acid, erucic acid, lauric acid, ethylene bisstearic acid, ethylene bisoleic acid, alkanoic acid, etc.) with amines (ethylenediamine, diethylenetriamine, triethylenetetramine, polyethylenepolyamine, etc.). When amide is used as the thixotropy-imparting agent, the content of amide (the mass of only amide excluding solvent when amide paste or the like is used, i.e., the content in solid content) is preferably 0.1% by mass or more and 5% by mass or less, more preferably 0.4% by mass or more and 3% by mass or less, and even more preferably 0.9% by mass or more and 2% by mass or less.

[0030] Hereinafter, a method for preventing peeling, which is a main application of the one-component urethane resin composition according to this embodiment, will be described. In the spalling prevention method according to the present embodiment, for example, as shown in FIG. 1, the one-component urethane resin composition described above is applied to the surface of a concrete structure or a wall surface to which tiles are attached, and then dried to form a spalling prevention layer, thereby preventing the concrete pieces or tiles from spalling.

[0031] Specifically, the peeling prevention method according to this embodiment includes the following steps. First, dust and foreign matter adhering to the surface of the concrete structure or the wall surface to which tiles are attached is removed. At this time, if there are protrusions or steps on the surface of the concrete structure, it is preferable to smooth the surface. Next, a primer is applied to the surface of the concrete structure and dried to form a primer layer. The method of applying the primer to the surface of the concrete structure is not particularly limited, but examples thereof include a method of spraying the primer with a spray gun, and a method of applying the primer with a roller, a brush, or a rake. After forming the primer layer, the one-liquid type urethane resin composition according to the present embodiment is applied and dried to form a peeling prevention layer. The method of applying the one-liquid type urethane resin coating composition is not particularly limited, but examples thereof include application by a roller, a trowel or a rake. After the peeling-preventing layer is formed, a top coat may be further applied to the surface of the peeling-preventing layer by a spray gun or the like to form a top coat layer.

[0032] As the primer, any type can be used, regardless of whether it is one-component or two-component, and regardless of whether it is water-based or solvent-based, but for example, one or more of urethane resin-based, urea resin-based, epoxy resin-based, acrylic resin-based, modified silicone resin-based, silicone-based, and inorganic primers can be used. Among them, it is preferable to use an acrylic silicone resin-based primer. As the top coat, any type of primer can be used, whether it is one-component or two-component, and whether it is water-based or solvent-based, and for example, one or more of urethane resin-based, urea resin-based, epoxy resin-based, acrylic resin-based, modified silicone resin-based, silicone-based, and inorganic primers can be used. Among them, it is preferable to use an acrylic silicone resin-based primer.

[0033] The thickness of the anti-exfoliation layer formed by the above-mentioned method can be appropriately changed depending on the purpose and environment, but for example, it is preferably 0.10 mm or more and 10 mm or less, more preferably 0.15 mm or more and 8 mm or less, and even more preferably 0.20 mm or more and 5 mm or less.

[0034] The primer layer and the topcoat layer are not essential components, and only one of them may be formed as necessary, or neither of them may be formed. If necessary, a reinforcing material such as glass cloth and / or a fiber-knitted mesh can be embedded in the resin coating film in the peel-off prevention layer. In this case, after applying a primer to the wall surface or applying a one-component urethane resin composition once, a mesh or the like is attached, and then the one-component urethane resin composition is applied from above so as to cover the mesh, and then the mesh can be embedded by drying. As the reinforcing material, a wide variety of materials can be used, including biaxial or triaxial mesh sheets containing synthetic fibers, carbon fibers, glass fibers, metals, etc., woven or woven synthetic fibers, or synthetic resin nets, etc. More specifically, glass cloth, vinylon fiber nets, aramid fiber nets, aramid sheets, carbon sheets, metal meshes, etc. can be mentioned.

[0035] <Effects of this embodiment> By using the resin composition according to this embodiment in the above-mentioned peeling prevention method, it is possible to form a peeling prevention layer that exhibits strength due to urethane bonds, has excellent curing properties, and also has sufficient weather resistance. Furthermore, since the one-liquid type urethane resin composition contains additives such as a thixotropy-imparting agent in an appropriate range, the workability when applying the one-liquid type urethane resin composition to a wall surface can be improved.

[0036] The present invention is not limited to the above-described embodiment, and various modifications and combinations of the embodiments may be made without departing from the spirit of the present invention. For example, the one-component urethane resin composition according to the present invention can be used not only in the above-mentioned peeling prevention method, but also in a wide range of applications requiring similar curing strength, curing properties, and weather resistance. EXAMPLES

[0037] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these.

[0038] <Synthesis of urethane prepolymer> First, a urethane prepolymer was synthesized as follows. Synthesis Example 1 (Synthesis of urethane prepolymer P1) In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen seal tube and a heating / cooling device, 3267 g of polyoxypropylene diol (Actocol D-2000, average molecular weight 2000, manufactured by Mitsui Chemicals, Inc.) was charged while flowing nitrogen gas, and 648.61 g of isophorone diisocyanate (IPDI, manufactured by Sumika Covestro Urethane Co., Ltd., trade name Desmodur I, molecular weight 222.3) and 0.783 g of zirconium octanoate (manufactured by Hope Pharmaceutical Co., Ltd., 17% Octope Zr) as a reaction catalyst were charged while stirring, and the reaction was carried out at 80°C to 90°C for 3 hours, and the reaction was terminated when the content of isocyanate groups became less than the theoretical value (2.763 mass%), synthesizing urethane prepolymer P1. The obtained urethane prepolymer P1 was a transparent viscous liquid at room temperature with an isocyanate group content of 2.6387 mass% measured by titration. Synthesis Examples 2 to 4 (Synthesis of Urethane Prepolymers P2 to P4) Urethane prepolymers P2 to P4 were synthesized in the same manner as in Synthesis Example 1, except that the raw materials and the charging ratios (molar ratios) were changed as shown in Table 1. The polyols in the table are as follows. Here, a polyol with an average molecular weight of 2000 is used as an example, but the average molecular weight of the polyol can be changed as appropriate, and similar results can be obtained even when a polyol with an average molecular weight of 1000, 3000, 4000, etc. is used. <Polyol> PTG-L2000: Modified polytetramethylene glycol, average molecular weight 2000, manufactured by Hodogaya Chemical Co., Ltd. PTMG2000: Polytetramethylene glycol, average molecular weight 2000, manufactured by Mitsubishi Chemical Corporation

[0039] [Table 1]

[0040] <Preparation of one-component urethane resin composition> Example 1 In a kneading vessel equipped with a stirrer, a heating device, a cooling device, and a nitrogen-sealed tube, 1358.8 g of the urethane prepolymer P1 obtained in Synthesis Example 1, 26.1 g of hydrogenated XDI (Takenate 600, manufactured by Mitsui Chemicals), 338.7 g of IPDI isocyanurate (Desmodur Z4470BA, manufactured by Sumika Covestro Urethanes), 648.9 g of a urethane bond-containing oxazolidine compound (M-OZ-T4(80) manufactured by Mitsui Chemicals), 222.7 g (amide content: 20%) of amide wax (Disparlon F-9050, manufactured by Kusumoto Chemicals), 39.5 g of a neutral hindered amine-based light stabilizer (Tinuvin 123 pKb = 9.6, manufactured by BASF), 1.0 g of a hydroxyphenyl triazine-based ultraviolet absorber (Triphenyl 123 pKb = 9.6, manufactured by BASF), and 1.0 g of a hydroxyphenyl triazine-based ultraviolet absorber (Triphenyl 123 pKb = 9.6, manufactured by BASF) were mixed under nitrogen gas flow. A one-component urethane resin composition was prepared by adding 39.5 g of ethyl acetate (Tinuvin 400), 32.4 g of polyether phosphate ester (Disparlon 3500, manufactured by Kusumoto Chemical Industries Co., Ltd.), 4.02 g of a silicone antifoaming agent (BYK-066N, manufactured by BYK-Chemie Co., Ltd.), 47.6 g of diethylene glycol dimethyl ether (Hisorb MDM, manufactured by Toho Chemical Industry Co., Ltd.), and 294.3 g of a naphthenic solvent (Exsol D40, manufactured by Ando Parachemie Co., Ltd.), mixing well, degassing under reduced pressure, filling into a container and sealing it. Examples 2 to 11 and Comparative Examples 1 to 5 A one-component urethane resin composition was prepared in the same manner as in Example 1, except that the raw materials and the charging ratios (mass ratios) were changed as shown in Table 2. The thixotropy-imparting agent, hindered amine-based light stabilizer, curing accelerator, and solvent in Table 2 are as follows. <Thixotropic Agent> Disparlon 6820-20M: Amide wax (amide content: 20%) manufactured by Kusumoto Chemicals Aerosil RY-200S: Dimethylpolysiloxane-treated fumed silica manufactured by Nippon Aerosil Co., Ltd. <Hindered amine light stabilizer> Tinuvin 292: BASF basic hindered amine light stabilizer (pKb=5.1) <Curing accelerator> JP-504: Acid phosphate ester (butyl acid phosphate) manufactured by Johoku Chemical Industry Co., Ltd. JP-508: Acid phosphate ester (2-ethylhexyl acid phosphate) manufactured by Johoku Chemical Industry Co., Ltd. JP-513: Acid phosphate ester (isotridecyl acid phosphate) manufactured by Johoku Chemical Industry Co., Ltd. Salicylic acid: Mitsui Fine Chemicals <Solvent> Dowanol PMA: Dow Chemical Japan Propylene glycol methyl ether acetate

[0041] The one-component urethane resin compositions prepared as described above and their cured products were evaluated for viscosity, weather resistance, tack-free time immediately after production, and tack-free time after accelerated exposure at 50°C for 2 weeks using the following evaluation methods. The results are shown in Table 2.

[0042] [Viscosity measurement] The viscosity of the prepared one-component urethane resin composition was measured using a B-type viscometer manufactured by Toki Sangyo Co., Ltd. The rotor used was a No. 3 rotor. The measurement temperature was 23°C. The viscosity was measured at rotation speeds of 20 rpm and 2 rpm, and the viscosity at a rotation speed of 2 rpm was divided by the viscosity at a rotation speed of 20 rpm to obtain the thixotropy index (TI). A TI value of 3 or more was determined to be good workability.

[0043] [Evaluation of tack-free time] The prepared one-liquid urethane resin composition was flattened to a thickness of 0.3 mm on a smooth glass plate using a spatula to prepare a test specimen, which was then left to stand in an atmosphere of 23°C ± 2°C and 50±10% relative humidity. The surface of the test specimen was lightly touched with a fingertip cleaned with DMC, and the time required from flattening to when the curable composition no longer adhered to the fingertip was measured and recorded as the tack-free time. The delay time of the tack-free time after 2 weeks of accelerated exposure at 50°C (corresponding to after half a year of storage in a general environment) relative to the measured tack-free time immediately after production (i.e., the difference between the tack-free time before and after storage) was evaluated according to the following criteria. 〇: The delay in tack-free time after storage is less than 10 minutes ×: The delay in tack-free time after storage is 10 minutes or more.

[0044] [Table 2]

[0045] Next, the strength and weather resistance of the cured products obtained by curing each of the one-component urethane resin compositions of Examples 1 and 5 were examined by the following methods. The results are shown in Table 3. [Film properties (tensile strength (N / mm 2 ) Elongation at break (%) Evaluation method] The tensile strength (N / mm 2 The evaluation was carried out by measuring the elongation at break (%) and the compressive strength at break (%). A coating film was prepared using the one-component urethane resin composition according to each Example and Comparative Example. The coating film was prepared by curing for 168 hours in an atmosphere of a temperature of 23°C ± 2°C and a relative humidity of 50 ± 10%, and test pieces were cut out using a dumbbell No. 3 shape as specified in JIS K 6251. The tensile performance test was performed by setting the tensile speed of the tensile tester to 200 mm / min.

[0046] [Table 3]

[0047] [Accelerated weather resistance evaluation method] The evaluation was performed by conducting an accelerated exposure test using a metal weather meter (black panel temperature: 63°C, shower 2 minutes / 120 minutes, manufactured by Daipla Wintes Co., Ltd.). The test pieces were prepared by applying the one-component urethane resin compositions according to Examples 1 to 6 to tiles at a rate of 600 g / m 2The coating was applied, cured and aged for 7 days under standard conditions of 23°C and 50% relative humidity, and then subjected to an accelerated exposure test. After 100 hours of accelerated exposure, the test pieces were visually observed, and were rated as ◯ if there was no whitening, cracking, or discoloration, and ◯ if there was whitening, cracking, or discoloration. Accelerated weather resistance evaluation was performed on Examples 1 to 6, and the results were ◯ for all of these Examples.

[0048] From the above results, it can be seen that the one-component urethane resin composition according to each Example using a neutral hindered amine light stabilizer (TINUVIN123, pKb=9.6) has sufficient strength and weather resistance for use in a method for preventing the peeling of concrete structures and tile exterior walls, and that no delay in the curing speed occurs, and that the curing speed can be maintained sufficiently fast, as can be seen from a comparison of the tack-free time immediately after production and after 2 weeks of accelerated exposure at 50°C. On the other hand, it can be seen that the curing properties of Comparative Examples 1 to 5 using a basic hindered amine light stabilizer (TINUVIN292, pKb=5.1) are poor, as can be seen from a comparison of the tack-free time immediately after production and after 2 weeks of accelerated exposure at 50°C. Furthermore, a comparison of Examples 1 to 10 with Example 11 revealed that the addition of a thixotropy-imparting agent can adjust the viscosity of the one-component urethane resin composition to within an optimal range for workability when applying with a brush. It has been confirmed that the hydrogenated XDI, UV absorbers, antioxidants, and silicon-based defoamers listed in Table 2 exhibit similar performance in terms of the various indicators evaluated in this study even when these are not added.

Claims

1. An isocyanate group-containing urethane prepolymer (A); A compound (B) having an oxazolidine ring; A neutral hindered amine light stabilizer (C); an acidic hardening accelerator (D); A one-component urethane resin composition comprising:

2. The one-component urethane resin composition according to claim 1, further comprising a thixotropy-imparting agent (E).

3. 3. The one-component urethane resin composition according to claim 2, wherein the thixotropy-imparting agent (E) contains silica or an amide.

4. 2. The one-component urethane resin composition according to claim 1, wherein the acidic curing accelerator (D) is an acidic phosphate ester compound (D-1).

5. 5. The one-component urethane resin composition according to claim 4, wherein the acidic phosphate ester compound (D-1) is a polyether phosphate ester.

6. A method for preventing spalling, comprising the step of applying the one-component urethane resin composition according to any one of claims 1 to 5 to a concrete structure and / or a wall surface to which tiles are attached, to form a spalling prevention layer that prevents concrete pieces and / or tiles from spalling from the wall surface.

7. 7. The method for preventing peeling according to claim 6, further comprising the step of applying a primer to the wall surface to form a primer layer before applying the one-component urethane resin composition.

8. The peeling prevention method according to claim 6, further comprising the step of forming a topcoat layer by applying a topcoat onto the peeling prevention layer after forming the peeling prevention layer.

9. 7. The method for preventing peeling according to claim 6, characterized in that a glass cloth and / or a fiber knitted mesh is placed on the wall surface, and then the one-component urethane resin composition is applied to form a peeling prevention layer in which the glass cloth and / or the fiber knitted mesh is embedded.

Citation Information

Patent Citations

  • Curable composition

    JP2007063551A

  • One component type polyurethane resin composition for preventing falling of concrete pieces or tiles and a method for preventing falling of concrete pieces or tiles using the same

    JP2011252292A